Influence of Organisational Culture on Strategy Execution in a South African Organisation - Reddy, Melissa; Scheepers, Caren (Journal of Applied Business Research, 2019)
Purpose: This study examines the effects of nine dimensions of organisational culture (uncertainty avoidance; gender egalitarianism; assertiveness; institutional collectivism; in-group collectivism; humane, future and achievement orientation; and power distance) on the dimensions of strategy execution (information sharing, leadership, rewards, performance, structure, employee commitment and coordination) within a fast-moving consumer goods (FMCG) company.Design: A survey questionnaire covering demographics, organisational culture and strategy execution was distributed electronically. Following assessment of reliability and validity of the 281 completed questionnaires, Pearson correlation and a canonical correlation analyses were conducted using the nine dimensions of culture as predictors of strategy execution variables, to evaluate the multivariate shared relationship between the two variable sets.Findings: The findings indicate that the dimensions of organisational culture have a variation of strong, medium and weak associations with the dimensions of strategy execution. Achievement orientation was found to have the highest effect on strategy execution dimensions and the future planning orientation the second highest.Research limitations/implications: The major limitation was that the population was represented by one large organisation in the South African FMCG industry, thereby excluding other companies in this country and the results may not necessarily be generalised to other populations. Future studies could include more industries and countries.Practical implications: This study provides evidence that company management must place considerable emphasis on developing organisational culture dimensions that have a positive impact on strategy execution.Originality/value: The study reveals that achievement and future planning orientated cultures have a significant influence on strategy execution.
Keywords: business; research; Organisational Culture; Strategy Execution; Dimensions; Achievement Culture; Hofstede